Cardiovascular adverse events associated with immune checkpoint inhibitors: a meta-analysis - Li, Xi; Li, Dan (Frontiers in Immunology, 2024)
Objective: To evaluate the cardiovascular safety of anticancer drug immune checkpoint inhibitors (ICIs) used in patients with malignant tumors. Methods: Four clinical research databases that have been completed since their establishment were searched, and the odds ratios and 95% confidence intervals of each indicator were statistically calculated. Results: 62 randomized controlled trial and controlled trials were included. In single drug treatment ICIs group, the overall risk of cardio cerebral Vascular disease at all levels was higher than that in the placebo/chemotherapy group. Especially in all grades of Myocarditis and above grade 3 compared with normal controls, except for pericardial lesions, other indicators have no obvious side effects. Conclusion: Single drug use of an anti-tumor ICIs may increase cardiovascular side effects risk in cancer patients, so we need to strengthen monitoring, identification and management, and timely intervention to manage ICI induced adverse events. a detailed evaluation of the patient's basic cardiovascular condition should be conducted before using this drug.